Testing the applicability of the low-cost carrier model in East African aviation market: A gravity demand model analysis - Samunderu, Eyden; Kandel, Posada (BOHR International Journal of Operations Management Research and Practices, 2024)
Although there exists extensive literature on the demand patterns and long-term sustainability of low-cost carriers from numerous perspectives and in different markets, no research has examined its applicability to the East African aviation context. Therefore, this study aims to fill this gap by examining whether the European low-cost model can be sustainable against the backdrop of the challenges and complexities of the East African aviation environment. This article draws its theoretical literature assessment from the pillar of European low-cost carriers and gives a scope of the underlining strategic implications of operating a low-cost carrier model. Against such a backdrop, the African aviation market’s operational complexities, challenges and opportunities, and demand patterns are presented in order to draw a conclusive evidence on whether a low-cost carrier in its current existence can be adopted in the East African market. Hypothetically, sufficient demand levels generally present the main barrier to operating an airline because, without revenue-paying passengers, operating costs cannot be covered. Subsequently, natural and latent demand levels on sample routes between the studied countries’ major cities are forecasted using gravity modeling in order to determine whether current and future demand levels are sufficient to justify direct point-to-point flights between city-pairs on an aircraft at a typical European low-cost seating density. The findings suggest that latent demand could be stimulated on most routes by reducing ticket costs, thus justifying direct point-to-point services between the studied city-pairs on a typical European low-cost configured aircraft. Some routes, however, showed resilience to demand stimulation through airfare reduction. The study also includes a survey analysis of the general travel behavior of coach passengers in the East African market in order to understand their likelihood of switching from road transportation to air transportation. The findings underpinned the results found in the theoretical demand modeling.